An AP‐DE Algorithm Based on Multi‐step Gradient Method. Issue 1 (1st January 2016) - Dai, Dameng; Mu, Dejun
Abstract : Aim to improve the convergence of the adaptive filtering, based on the multi‐step gradient method, a new affine projection algorithm with direction error is presented. The statistical behavior of the proposed algorithm is analyzed. The deterministic recursive equations for the weight error and for the Mean‐square error (MSE) are derived in the weight update direction of the adaptive filtering. The steady‐state MSE is also obtained. Simulation results show that the proposed algorithm improve the adaptive filtering convergence and corroborate the theoretical analytical results.